Decomposition behavior of gaseous ruthenium tetroxide under atmospheric conditions assuming evaporation to dryness accident of high-level liquid waste. Issue 11 (1st November 2020) - Yoshida, Naoki; Ono, Takuya; Yoshida, Ryoichiro; Amano, Yuki; Abe, Hitoshi
ABSTRACT: Emphasis has been placed on the behavior of ruthenium (Ru) in the evaporation to dryness accident due to the loss of cooling functions (EDLCF) of high-level liquid waste in fuel reprocessing plants. It is because Ru would form volatile compounds such as ruthenium tetroxide (RuO4 ) and could be released into the environment with other coexisting gasses such as nitric acid (HNO3 ), water (H2 O). To contribute to the safety evaluation of this accident, we experimentally evaluated the decomposition and chemical change behavior of the gaseous RuO4 (RuO4 (g)) under the various atmospheric conditions: temperature and composition of coexisting gasses. As a result, the behavior of the RuO4 (g) was diverse depending on the atmospheric conditions. In the experiments with the dry air or H2 O vapor, decomposition of RuO4 (g) was observed. In the experiment with the mixed gas which containing HNO3, almost no decomposition of the RuO4 (g) was observed, and chemical form of the RuO4 (g) was retained.